The masses are revolting : Victorian culture and the political aesthetics of disgust - Samalin, Zachary (Cornell University Press, 2021)
"The Masses Are Revolting is a history of disgust in nineteenth-century Britain. It focuses on the role of disgust in various cultural domains, such as sanitary reform, obscenity law, realist literature, and urban sociology"--